2019
DOI: 10.12680/balneo.2019.306
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation protocol with or without mobile health in overweight and obese knee osteoarthritis patients - a pilot study

Abstract: Knee osteoarthritis (OA) is a degenerative and weight bearing joint disease that resulted from wear and tear of articular cartilage. It is more common in the overweight and obese knee OA patients. The objectives of pilot study were to assess the feasibility, acceptability and challenges of study design, study setting and tools of lower limb rehabilitation protocol among the knee OA patients who are overweight and obese. Twelve overweight and obese knee OA patients attending a Teaching Bay in the Pakistan were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

6
0

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The IDC is explained elsewhere. 18 All patients were also given a diary and asked to record the attendance of completion their interventions based on leaflets.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The IDC is explained elsewhere. 18 All patients were also given a diary and asked to record the attendance of completion their interventions based on leaflets.…”
Section: Methodsmentioning
confidence: 99%
“…The progressive resistance strength training of LLRP were also translated into Urdu language by two language experts because the patients demanded the need of Urdu translation in a pilot study. 18 This LLRP was consisted of a 45–60 minutes training session followed by 10 minutes’ warm-up at the start and 10 minutes cool down at the end of the training session. The frequency, intensity, and duration of training sessions of non-weight bearing progressive resistance strength training of the LLRP are explained in Supplementary Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A current systematic review on nonpharmacological interventions for treating symptoms of knee OA in overweight or obese patients concluded that strengthening exercise played a vital role in relieving knee pain and improving function [14]. Non-pharmacological interventions, primarily strengthening exercise and more recently strengthening exercises of the lower limb rehabilitation protocol (LLRP) in non-weight-bearing positions, are recommended as the first line of treatment among overweight or obese knee OA patients [15].…”
Section: Introductionmentioning
confidence: 99%